Increasing the Results and Interest in Learning Civics through a Problem-Based learning Model for 1st Grade Students - Wardani, Niken Tri (Universitas Sebelas Maret, 2022)
The purpose of this study was to improve Civics learning outcomes through the Problem Based Learning method for students of SD Negeri Ngemplak class, Karangnongko, Klaten Semester I of the 2021/2022 academic year. The subjects in the study were the process and learning outcomes of Civics in grade 1 students of SD Negeri Ngemplak, Karanongko, Klaten. semester I of the 2021/2022 academic year consisting of 19 students, namely 10 boys and 9 girls. The research procedure used is a classroom action research type procedure which is carried out in 2 cycles, each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. Data analysis, qualitative data from observations of the learning process were analyzed using qualitative descriptive analysis by comparing cycle I with cycle II, while data in the form of numbers (quantitative data) from student learning outcomes were analyzed using comparative descriptive namely comparing initial condition test scores, cycle I test scores and cycle II test scores, then reflected. The results showed that through the Problem Based Learning method, it can improve the achievement of Civics learning outcomes for Grade 1 students of SD Negeri Ngemplak, Karangnongko, Klaten Semester I of the 2021/2022 academic year. The learning process of Civics material on the Formulation Process of Pancasila from cycle I to cycle II has improved: student learning outcomes from cycle I to cycle II have increased, namely from 8 students (72.7%) who got a complete score to 11 students (100%). There was an increase of 3 students (27.3%) and the class average score from 77.8 to 83.5 increased by 5.7.